2015
DOI: 10.5935/1518-0557.20150031
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Serum Progesterone Levels on the Results ofIn VitroFertilization Treatments: A Literature Review

Abstract: The aim of this review is to analyze the relationship between preovulatory progesterone (P) rise and in vitro fertilization (IVF) pregnancy outcomes. It also investigates the sources and effects of rises in progesterone levels, including the underlying mechanisms and potential strategies in preventing its elevation during ovarian stimulation. Progesterone is produced in the early follicular phase in the adrenal gland, which shifts toward the ovaries prior to ovulation. Several factors contribute to the etiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…In this and other studies, serum P4 concentration was greater in FSH-treated than nontreated ewes at early and mid-luteal phases in sheep [91]. Similar effects of ovarian hyperstimulation or superovulation on peripheral P4 concentration have been reported for other species including humans and cows [40,44,[77][78][79]92]. Such differences between hyperstimulated vs. non-stimulated females are due to greater number of CL after gonadotropin treatment.…”
Section: Revised 12supporting
confidence: 82%
See 1 more Smart Citation
“…In this and other studies, serum P4 concentration was greater in FSH-treated than nontreated ewes at early and mid-luteal phases in sheep [91]. Similar effects of ovarian hyperstimulation or superovulation on peripheral P4 concentration have been reported for other species including humans and cows [40,44,[77][78][79]92]. Such differences between hyperstimulated vs. non-stimulated females are due to greater number of CL after gonadotropin treatment.…”
Section: Revised 12supporting
confidence: 82%
“…The effects of gonadotropin treatments on uterine functions affecting endometrial receptivity have been clearly demonstrated for humans and other mammalian species [38]. For example, in humans, gonadotropin treatment resulted in alterations of mRNA expression of receptors for steroids, and other hormones and growth factors in the endometrium, and in steroid serum concentrations [40,41,[77][78][79]. In cows, treatments with gonadotropins resulted in altered oocyte LD accumulation and blastocyst development, expression of genes that regulate metabolic activity of the embryo, serum profile of P4 and PG metabolites, milk E2 concentration, endometrial and embryonic gene expression, and uterine blood flow, secretory functions, morphology and vascular density [43][44][45][80][81][82][83][84].…”
Section: Revised 12mentioning
confidence: 99%
“…Such lines of evidence demonstrate that low‐dose hCG will not cause early onset of luteinization of granulosa cells, which is recognized as an injury to the quality of oocytes. In other words, low‐dose hCG has proved to be safe and does not impact upon implantation, although previously the premature luteinization of granulosa cells was thought to be the most possible limitation of hCG compared with r‐LH . In addition, it is observed that P4 rises visibly the day after trigger with a much higher value in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have demonstrated that elevated serum progesterone level during the follicular phase provides a suboptimal endocrine milieu for follicular growth and advances or disrupts endometrial receptivity. As a result, the pregnancy rate and live‐birth rate in fresh embryo transfer (ET) cycles are reduced …”
Section: Introductionmentioning
confidence: 99%
“…As a result, the pregnancy rate and live-birth rate in fresh embryo transfer (ET) cycles are reduced. [1][2][3] Even though the origin of serum progesterone throughout the follicular phase remains unclear, its production is a combination of secretion from the adrenals and the ovaries. [4][5][6] The adrenals are possibly the main source of serum progesterone during the early follicular phase, whereas the ovaries mainly contribute during the late follicular phase.…”
Section: Introductionmentioning
confidence: 99%